Laboratory based antimicrobial resistance surveillance for Pseudomonas aeruginosa blood isolates from South Africa - Lekalakala, M. R; Singh-Moodley, Ashika; Duse, Adriano; Naicker, Preneshni; Kularatne, Ranmini; Nana, Trusha; Mbelle, Nontombi; Dawood, Halima; Han, Khine Swe Swe; Ramjathan, Praksha; Bhola, Prathna; Whitelaw, Andrew; et al. (Journal of Infection in Developing Countries, 2018)
Introduction: Antimicrobial resistant bacterial infections are widespread globally and increases in antimicrobial resistance presents a major threat to public health. Pseudomonas aeruginosa is an opportunistic healthcare-associated pathogen with high rates of morbidity and mortality and an extensive range of resistance mechanisms. This study describes the antibiotic susceptibility profiles of P. aeruginosa isolates from patients with bacteraemia submitted by sentinel laboratories in South Africa from 2014 to 2015. Methodology: Organism identification and antimicrobial susceptibility testing were done using automated systems. Molecular methods were used to detect common resistance genes and mechanisms. Results: Overall the susceptibility was high for all antibiotics tested with a decrease over the two-year period. There was no change in the MIC50 and MIC90 breakpoints for all antibiotics from 2014 to 2015. The MIC50 was within the susceptible breakpoint range for most antibiotics and the MIC90 was within the susceptible breakpoint range for colistin only. Phenotypically carbapenem non-susceptible isolates harboured the following plasmid-mediated genes: blaVIM (n = 81, 12%) and blaGES (n = 6, 0.9%); blaNDM (n = 4, 0.6%) and blaOXA-48 and variants (n = 3, 0.45%). Porin deletions were observed in one meropenem non-susceptible isolate only, and multi-drug resistance efflux pumps were expressed in the majority of the non-susceptible isolates investigated. BlaVEB-1, blaIMP and blaKPC were not detected. Conclusion: The prevalence of resistance to commonly used antibacterial agents was low for P. aeruginosa isolates and similarly, tested resistance mechanisms were detected in a relatively small proportion of isolates. Findings in this study represent baseline information for understanding antimicrobial susceptibility patterns in P. aeruginosa isolates from blood. Our surveillance report may assist in contributing to hospital treatment guidelines.
Article published in the Journal of Infection in Developing Countries 2018; 12(8):616-624. doi:10.3855/jidc.9539
Keywords: Antimicrobial susceptibility testing; Resistance genes; Carbapenemases; Efflux pumps; Porins; Pseudomonas aeruginosa --South Africa